Pre-Service Teacher’s Experience in Teaching Descriptive Writing via Asyncrhonous Class during Covid-19 - Handhini Dewi Mustikah (Journal of English Language and Education, 2021)
This study aims at exploring the experience of pre-service English teacher in teaching descriptive writing via asynchronous class during covid-19 pandemic. The study was a descriptive case study where the phenomena or problem occurred to a pre-service teacher during teaching descriptive writing in teaching and training program. The participant in this study is one student college majoring English Education from Karawang. The data were collected by conducting interview. The result revealed that internet availability and accessibility were become a background of teaching via asynchronous, pre-service teacher faced several problems during teaching learning process such as didn’t know either students have learning motivation or not, anxiety toward students writing process, shortage of time in controlling the students, asynchronous class considered as a flexible learning because it can be conducted anywhere and anytime, and utilizing mobile application such as Youtube, Google Classroom, and Animaker as supporting media for pre-service teacher, writing process and build the students’ motivation during distance education.